2019
DOI: 10.2478/hjbpa-2019-0032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of System Quality, Information Quality, Service Quality on User Acceptance and Satisfaction and Its Impact on Net Benefits (Study of Information System Users Lecturer Performance Load (BKD) in Malang State University)

Abstract: This study aims to examine the influence of system quality, information quality, and service quality of the lecturer at Malang State University. This study will also investigate the effect on user satisfaction and its impact on net benefits for users of UM Information System Expenses. This study applies a modification of the information system success model from DeLone & McLean. The model is analyzed by modeling the Structural Equation Modeling (SEM) based on components or variants (component based) that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 16 publications
2
5
0
2
Order By: Relevance
“…The results showed that the user satisfaction variable had a positive and significant effect on the net benefit variable. These results are in line with the research of Widiastuti, Haryono and Said (2019), there is a user satisfaction which has a positive and significant influence on net benefits. The results of this study also support the success model of the Delone and Mclean information systems (2003) which states that user satisfaction has a positive and significant effect on net benefits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that the user satisfaction variable had a positive and significant effect on the net benefit variable. These results are in line with the research of Widiastuti, Haryono and Said (2019), there is a user satisfaction which has a positive and significant influence on net benefits. The results of this study also support the success model of the Delone and Mclean information systems (2003) which states that user satisfaction has a positive and significant effect on net benefits.…”
Section: Discussionsupporting
confidence: 91%
“…Previous research on user satisfaction has been carried out by several researchers, such as Amarin and Wijaksana (2021), Widiastuti, Haryono and Said (2019), Utomo et al (2017), Ferdini et al (2013 and Hidayat and Yusrawati (2012). However, in previous studies satisfaction was measured directly through system quality, information quality, and service quality.…”
mentioning
confidence: 99%
“…This shows that the quality of information on the implementation of APAPO has no significant effect on usage, and even tends to decrease. Widiastuti et al (2019) examined there is positive but not significant on the use of BKD system. Users judge the information obtained from the system, but the frequency of users accessing the BKD system is not frequent.…”
Section: The Hypothesis Analysis Apapo Using Delone and Mcleanmentioning
confidence: 80%
“…Hasil penelitian menjabarkan tingkatan dari ke-24 faktor-faktor tersebut dari paling tinggi hingga ke paling rendah pengaruhnya. 9 Penelitian lainnya yang dilakukan oleh Rini Widiastuti 10 Penelitian-penelitian terdahulu menjadi referensi dalam mengembangkan kuesioner untuk mengukur keberhasilan implementasi dari sistem informasi Surveilans Penyakit Tidak Menular di Kota Palembang. Peneliti menggunakan kuesioner yang digunakan pada penelitian oleh Putu Wuri Handayani, dkk, untuk kualitas sistem, kualitas informasi, dan kualitas pelayanan.…”
Section: ©2021 Jekk All Right Reservedunclassified